O. Auge u. a. (Hgg.): Fürsten an der Zeitenwende zwischen Gruppenbild und Individualität. Formen fürstlicher Selbstdarstellung und ihre Rezeption (1450–1550). Ostfildern 2009 - Moritz, Tilman (H-Soz-Kult)

R. Dauser u. a. (Hgg.): Wissen im Netz. Botanik und Pflanzentransfer in Korrespondenznetzen des 18. Jahrhunderts. Berlin 2008 - Moritz, Tilman (H-Soz-Kult)

Online Diarization of Streaming Audio-Visual Data for Smart Environments - Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (IEEE Journal of Selected Topics in Signal Processing)
For an environment to be perceived as being smart, contextual information has to be gathered to adapt the system's behavior and its interface towards the user. Being a rich source of context information speech can be acquired unobtrusively by microphone arrays and then processed to extract information about the user and his environment. In this paper, a system for joint temporal segmentation, speaker localization, and identification is presented, which is supported by face identification from video data obtained from a steerable camera. Special attention is paid to latency aspects and online processing capabilities, as they are important for the application under investigation, namely ambient communication. It describes the vision of terminal-less, session-less and multi-modal telecommunication with remote partners, where the user can move freely within his home while the communication follows him. The speaker diarization serves as a context source, which has been integrated in a service-oriented middleware architecture and provided to the application to select the most appropriate I/O device and to steer the camera towards the speaker during ambient communication.
Keywords: audio streaming; audio visual data streaming; context information speech; face identification; face recognition; image segmentation; middleware; multimodal telecommunication; online diarization; service oriented middleware architecture; sessionless telecommunication; software architecture; speaker identification; speaker localization; speaker recognition; steerable camera; telecommunication computing; temporal segmentation; terminal-less telecommunication; video streaming

Visual Jazz. Performative Mittel afroamerikanischer Identitätsrepräsentation in Dudley Murphys ST. LOUIS BLUES und BLACK AND TAN FANTASY (1929) - Münzmay, Andreas (Kieler Beiträge zur Filmmusikforschung)
Dass die Filmgeschichte des frühen Jazz in weiten Teilen noch Forschungsdesiderat geblieben ist, ist insofern erstaunlich, als die performative Komponente – der Auftritt als solcher, aber genauso die mediale Bannung und Verfügbarmachung des 'unwiederholbaren Moments' - unbestritten als eines der wichtigsten Charakteristika von Jazz gilt. Vorrangiges Medium der Speicherung von Jazzgeschichte sind selbstverständlich die Tonträger. Hinsichtlich der Performance von Jazz - also der körperlichen, Identität vorstellenden oder konstruierenden Präsenz der Musikerin/des Musikers - sind aber gerade Bildmedien und insbesondere Filmkunstwerke aussagekräftige Auskunftgeber (Gabbard 2003). Zu den frühesten tonfilmischen Jazzdokumenten gehören die beiden Jazz-Kurzfilme, die Dudley Murphy im Jahr 1929 für RKO schrieb und drehte: die musical shorts 'St. Louis Blues' mit Bessie Smith (Premiere: New York Ende August 1929) und 'Black and Tan Fantasy' mit Duke Ellington (Premiere: New York 8. Dezember 1929)

Bolzano, Bernard, Philosophische Tagebücher 1803–1810. Erster Teil, hg. v. Jan Berg (Bernard Bolzano-Gesamtausgabe. Reihe II. B.14), Friedrich Frommann Verlag-Günther Holzboog: Stuttgart-Bad Cannstatt 2009 - Peckhaus, Volker (zbMATH Open, Zbl. 1181.01029)

Bolzano, Bernard, Philosophische Tagebücher 1803–1810. Zweiter Teil, hg. v. Jan Berg (Bernard Bolzano-Gesamtausgabe. Reihe II. B.15), Friedrich Frommann Verlag-Günther Holzboog: Stuttgart-Bad Cannstatt 2009 - Peckhaus, Volker (zbMATH Open, Zbl. 1181.01030)

De Risi, Vincenzo, Geometry and Monadology. Leibniz’s Analysis Situs and Philosophy of Space, Birkhäuser: Basel/Boston/Berlin 2007 (Science Networks. Historical Studies; 33) - Peckhaus, Volker (zbMATH Open, Zbl. 1180.51002)

Editorial - Peckhaus, Volker (History and Philosophy of Logic)

Degen, J.W., “Variations of Frege’s Grundgesetze”, Travaux de logique 18 (2007), 15–31 - Peckhaus, Volker (zbMATH Open, Zbl. 1194.03008)

Almog, Joseph, “Frege’s Puzzles”, Journal of Philosophical Logic 37 (2008), 549–574 - Peckhaus, Volker (zbMATH Open, Zbl. 1178.03004)

Music Encoding Initiative Tag Library, 2010-05 Release - Kepper, Johannes; Roland, Perry D.

Making Worlds. Epistemological, Ontological and Political Dimensions of Technoscience - Weber, Jutta (Poiesis and Praxis. International Journal of Ethics of Science and Technology Assessment 1/2010)

Armchair Warfare ‘on Terrorism’. On Robots, Targeted Assassinations and Strategic Violations of International Law - Weber, Jutta (Thinking Machines and the Philosophy of Computer Science: Concepts and Principles)

Technikwissenschaft / Technowissenschaft - Weber, Jutta (Enzyklopädie Philosophie Bd. 3)

Strong NP-hardness of the quantum separability problem - Gharibian, Sevag (Quantum Information & Computation)
Given the density matrix rho of a bipartite quantum state, the quantum separability problem asks whether rho is entangled or separable. In 2003, Gurvits showed that this problem is NP-hard if rho is located within an inverse exponential (with respect to dimension) distance from the border of the set of separable quantum states. In this paper, we extend this NP-hardness to an inverse polynomial distance from the separable set. The result follows from a simple combination of works by Gurvits, Ioannou, and Liu. We apply our result to show (1) an immediate lower bound on the maximum distance between a bound entangled state and the separable set (assuming P != NP), and (2) NP-hardness for the problem of determining whether a completely positive trace-preserving linear map is entanglement-breaking.

Co-editor of the special issue “Capitalist crisis, communication & culture“ - Fuchs, Christian; Schafranek, Matthias; Hakken, David; Breen, Marcus (tripleC (cognition, communication, co-operation))

Theoretical Foundations of the Web: Cognition, Communication, and Co-operation. Towards an Understanding of Web 1.0, 2.0, 3.0 - Fuchs, Christian; Hofkirchner, Wolfgang; Schafranek, Matthias; Raffl, Celina; Sandoval, Marisol; Bichler, Robert (Future Internet)

Capitalist Crisis, Communication, & Culture – Introduction to the Special Issue of tripleC - Fuchs, Christian; Schafranek, Matthias; Hakken, David; Breen, Marcus (tripleC (Cognition, Communication, Co-operation): Journal for a Global Sustainable Information Society)

Efficient implementation of the GW approximation within the all-electron FLAPW method - Friedrich, Christoph; Blügel, Stefan; Schindlmayr, Arno (Physical Review B)
We present an implementation of the GW approximation for the electronic self-energy within the full-potential linearized augmented-plane-wave (FLAPW) method. The algorithm uses an all-electron mixed product basis for the representation of response matrices and related quantities. This basis is derived from the FLAPW basis and is exact for wave-function products. The correlation part of the self-energy is calculated on the imaginary-frequency axis with a subsequent analytic continuation to the real axis. As an alternative we can perform the frequency convolution of the Green function G and the dynamically screened Coulomb interaction W explicitly by a contour integration. The singularity of the bare and screened interaction potentials gives rise to a numerically important self-energy contribution, which we treat analytically to achieve good convergence with respect to the k-point sampling. As numerical realizations of the GW approximation typically suffer from the high computational expense required for the evaluation of the nonlocal and frequency-dependent self-energy, we demonstrate how the algorithm can be made very efficient by exploiting spatial and time-reversal symmetry as well as by applying an optimization of the mixed product basis that retains only the numerically important contributions of the electron-electron interaction. This optimization step reduces the basis size without compromising the accuracy and accelerates the code considerably. Furthermore, we demonstrate that one can employ an extrapolar approximation for high-lying states to reduce the number of empty states that must be taken into account explicitly in the construction of the polarization function and the self-energy. We show convergence tests, CPU timings, and results for prototype semiconductors and insulators as well as ferromagnetic nickel.

Training participation of an aging workforce in an internal labor market - Pfeifer, Christian; Janssen, Simon; Yang, Philip; Backes-Gellner, Uschi